Personalised inpatient multidisciplinary rehabilitation elicits clinically relevant improvements in physical function in patients with multiple sclerosis – The Danish MS Hospitals Rehabilitation Study. Issue 1 (February 2021) - Hvid, Lars G; Gaemelke, Tobias; Dalgas, Ulrik; Slipsager, Mette K; Rasmussen, Peter V; Petersen, Thor; Nørgaard, Michael; Skjerbaek, Anders G; Boesen, Finn
Purpose: Evidence of the effects of inpatient multidisciplinary rehabilitation (MDR) on physical function in patients with multiple sclerosis (MS) is limited, particularly whether clinically relevant improvements can be achieved. The aim of this study, therefore, was to investigate the effects of personalised inpatient MDR on the physical function of MS patients. Methods: Embedded in the Danish MS Hospitals Rehabilitation Study, a pragmatic study was performed in MS patients undergoing four weeks of inpatient MDR specifically targeting physical function. Outcomes were assessed at baseline (n = 142), at discharge (n = 137) and at six months follow-up (n = 126) using the six-minute walk test (6MWT), six-spot step test (SSST), five times sit to stand test (5STS), nine-hole peg test (NHPT), dynamic gait index (DGI) and 12-item MS walking scale (MSWS). Results: From Baseline-to-Discharge, significant and clinically relevant improvements were found in all measures of walking capacity (6MWT, SSST, 5STS, DGI and MSWS; p < 0.05) along with significant (but not clinically relevant) improvements in upper extremity function (NHPT; p < 0.05). Whilst comparable improvements were observed within subgroups of MS phenotype (relapsing-remitting [RR] vs. secondary + primary progressive [SP + PP]), disease severity (moderate [EDSS2.5–5.5 ] vs. severe [EDSS6.0–7.5 ]) and age (young/middle-aged [Age24–59 ] vs. old [Age60–65 ]), an attenuated adaptation was nevertheless observed for 6MWT in the most affected and vulnerable subgroups (i.e. SP + PP, EDSS6.0–7.5 and Age60–65 ). The significant improvements in walking capacity and upper extremity function persisted at six months follow-up but did not exceed anymore the thresholds regarded as clinically relevant. Conclusion: The results provide novel evidence that personalised inpatient MDR targeting physical function in MS patients elicits significant and clinically relevant improvements in physical function.